Development and Assessment of the Mechanical Properties of the Lightweight Brick Masonry Unit Utilizing Expanded Polystyrene Beads (EPB) - Muhammad Umair; Kazim Ali; Salman Khan; Muhammad Farhan Aslam; Huma Rahman; Sami Ullah (Journal of ICT, Design, Engineering and Technological Science, 2023)
The application of polystyrene beads as a sustainable substitute in the production of soil-based bricks is investigated in this study. The objective of the research is to evaluate the mechanical and thermal characteristics of soil-brick composites at ratios of 4%, 8%, and 12% that contain different amounts of polystyrene beads. The purpose of the study is to determine how the inclusion of polystyrene beads affects the final composite bricks' insulating properties and structural integrity. Initial results indicate that the addition of polystyrene beads noticeably affects the mechanical and thermal properties of the composite bricks. According to preliminary findings, insulating qualities may get better as polystyrene ratios rise, but maintaining structural integrity requires striking a compromise. The results of this study provide important new information on the feasibility of using earth bricks augmented with polystyrene as an energy- and environmentally-friendly building material. More research and optimization efforts are advised to improve the composition and overall performance of these composite bricks for use in sustainable buildings.